2006
DOI: 10.1200/jco.2006.24.18_suppl.10546
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between thymidylate synthase expression and p53 levels with the treatment of cyclophosphamide, methotrexate, 5-fluorouracil chemotherapy(CMF) versus docetaxel (TXT) in locally advanced carcinoma of the breast

Abstract: 10546 Background: Adjuvant chemotherapy is used in the treatment of breast carcinoma independently of axillar node involvement. Different drug combinations such as CMF, FAC, FEC are still used; recently new drugs such as TXT (NEJM 332:1004,1997) show activity and are used also in adjuvant chemotherapy. 5 Fluorouracil (5Fu), a drug involved in main therapeutic regimens, blocks Thymidylate Synthase (TS), an enzyme involved in the DNA synthesis. TS not only links its own mRNA, but also p53 mRNA, inhibiting post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Additionally, in a number of patients, continuous administration of pemetrexed has been found to decrease TS levels ( 32 ). Brandi et al ( 33 ) revealed that patients with low levels of TS and high levels of p53 responded better to docetaxel. Overall, these results indicate that low levels of TS may be associated with an improved breast cancer prognosis and response to chemotherapy administration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in a number of patients, continuous administration of pemetrexed has been found to decrease TS levels ( 32 ). Brandi et al ( 33 ) revealed that patients with low levels of TS and high levels of p53 responded better to docetaxel. Overall, these results indicate that low levels of TS may be associated with an improved breast cancer prognosis and response to chemotherapy administration.…”
Section: Discussionmentioning
confidence: 99%